The Late Medieval and Early Post-Medieval site of Župnijski dom in Šentvid pri Stični. Analysis of the pottery and animal remains - Porenta, Sašo; Štular, Benjamin; Toškan, Borut; Mileusnić, Zrinka; Dirjec, Janez (Arheološki vestnik, 2015)
This paper presents the findings of archaeological excavations at Župnijski dom in Šentvid pri Stični, where Medieval and Post-Medieval archaeological finds were discovered. The otherwise modest remains of the Early and High Medieval settlement are significant archaeologically. Most of the finds (17,284 pottery fragments) belong to the Late Medieval or Early Post-Medieval periods, which are amongst the least researched periods in Slovenian archaeology. The analysis of these finds (pottery typology and tableware analysis), therefore makes the site particularly significant in Slovenian archaeology, because it can serve as a starting point for further research into these periods.